Impact of Elevated Body Mass Index and Obesity on Long-term Surgical Outcomes for Patients With Degenerative Cervical Myelopathy: Analysis of a Combined Prospective Dataset. Issue 3 (February 2017) - Wilson, Jefferson R.; Tetreault, Lindsay A.; Schroeder, Gregory; Harrop, James S.; Prasad, Srinivas; Vaccaro, Alex; Kepler, Christopher; Sharan, Ashwini; Fehlings, Michael G.
Abstract : Study Design: Analysis of a combined prospective dataset. Objective: To evaluate the impact of preoperative body mass index (BMI) on surgical outcomes in degenerative cervical myelopathy (DCM). Summary of Background Data: Although elevated BMI has been shown to have a deleterious impact on outcomes after lumbar spine surgery, limited evidence is available regarding its impact in DCM. Methods: Analyses were completed using a combined North American/International prospective surgical DCM dataset from 26 participating centers. Outcome measures included Neck Disability Index (NDI), modified Japanese Orthopedic Association (mJOA) score, and Short Form- 36 (SF-36) scores at 1 year postoperatively. Bivariate and multivariable statistics were used to model the relationship between preoperative BMI, as both a continuous and categorical variable with these outcomes. Results: Of 757 patients, mean BMI was 27.3 (±5.7) with 17 patients (3.5%) underweight, 271 patients (35.8%) normal weight, 275 patients (36.3%) overweight, and 194 patients (25.7%) obese. Controlling for preoperative mJOA, NDI, smoking status, age, and sex, elevated BMI was associated with increased neck disability at 1 year ( P < 0.01). On average, NDI scores were 4.5 points higher (95% confidence interval, CI: 1.6–7.6) for overweight patients and 5.7 points higher (95% CI: 2.6–8.9) for obese patients compared with individuals of normal weight. Obese patients had 0.5 times odds (odds ratio, OR = 0.5, 95% CI: 0.3–0.8, P < 0.01) of showing improvement equal to the minimal clinically important difference of NDI compared with their normal weight counterparts. Although there were strong trends towards reduced SF-36 mental component scores and physical component scores with elevated BMI, no association was found between BMI and 1-year mJOA. Conclusion: Increased BMI, particularly obesity, was associated with increased postoperative disability. This represents a potentially modifiable risk factor which clinicians can target to optimize postoperative outcomes. Level of Evidence: 2